Assessing phytotoxicity and tolerance levels of ZnO nanoparticles on Raphanus sativus: implications for widespread adoptions - Samuditha, Pathirannahalage Sahan; Adassooriya, Nadeesh Madusanka; Salim, Nazeera (Beilstein Journal of Nanotechnology, 2024)
The escalating release of zinc oxide nanoparticles (ZnO NPs) into the environment poses a substantial threat, potentially leading to increased concentrations of zinc (Zn) in the soil and subsequent phytotoxic effects. This study aimed to assess the effects of ZnO NPs on Raphanus sativus (R. sativus) concerning its tolerance levels, toxicity, and accumulation. ZnO NPs were synthesized by the wet chemical method and characterized by powder X-ray diffraction (PXRD), Fourier-transform infrared (FTIR) spectroscopy, ultraviolet–visible (UV–vis) spectroscopy, dynamic light scattering (DLS), and scanning electron microscopy (SEM). The effect of ZnO NPs (70 nm) on R. sativus grown in coir was evaluated. The application of 1,000 mg/L of ZnO NPs resulted in a significant increase (p < 0.05) in soluble protein content, carbohydrates, chlorophyll a (Chl-a), chlorophyll b (Chl-b), total chlorophylls, carotenoids, and antioxidants by 24.7%, 58.5%, 38.0%, 42.2%, 39.9%, 11.2%, and 7.7%, respectively. Interestingly, this dose had no impact on the indole acetic acid (IAA) content. Conversely, the use of 2,000 mg/L of ZnO NPs in the same medium led to a significant reduction (p < 0.05) in soluble protein content by 23.1%, accompanied by a notable increase in IAA by 31.1%, indicating potential toxicity. The use of atomic absorption spectroscopy confirmed the internalization of zinc in seedlings, with a statistically significant increase (p < 0.05). In control plants without ZnO NPs, Zn concentration was 0.36 mg/g, while at the highest ZnO NPs tested dose of 10,000 mg/L, it significantly rose to 1.76 mg/g, causing leaf chlorosis and stunted seedling growth. This suggests potential health risks related to Zn toxicity for consumers. Given the adverse effects on R. sativus at concentrations above 1000 mg/L, caution is advised in the application and release of ZnO NPs, highlighting the importance of responsible practices to mitigate harm to plant life and consumer health. The study demonstrated the tolerance of R. sativus to high Zn levels, classifying it as a Zn-tolerant species.
Keywords: phytotoxicity; Raphanus sativus; ZnO nanoparticles; Zn tolerance; Zn toxicity